Risiko Fenomena Sosial Sumbangan Amal di Jalan Raya Jember Bagaikan Dua Mata Pisau - Muhammad Faisal Azka; Jenny Fernanda; Natanael Natanael (Journal of Social, Culture, and Language, 2023)
This research is based on social phenomena that exist in society, especially in the Jember-East Java area. The Islamic community in this area takes action to ask for charitable donations on the main road with the aim of repairing or building a mosque. They did this behavior on the grounds that the mosque's construction funds could continue. Judging from Islamic values, this behavior is actually not justified because begging even under the pretext of developing the house of Allah is a prohibited action. This social phenomenon is also not free from risks. The risk theory popularized by Ulrich Beck explains that society cannot be separated from the consequences that come from its own behavior. This study aims to dissect the social phenomenon of charitable donations on the highway with Ulrich Beck's theory of risk. This study uses a qualitative method with a phenomenological approach. Data collection techniques are carried out by means of observation, interviews, and documentation. The data analysis technique uses the triangulation method. The results of this study indicate that there are two risks that accompany the phenomenon of charitable donations on the highway, namely the construction of mosques will continue, but on the other hand the community will take dishonest actions, such as taking or putting large sums of money into their personal pockets. . Keywords: Charitable Donations, Islamic Society, Risk, and Social phenomena